Exopolysaccharides from Microalgae and Cyanobacteria: Diversity of Strains, Production Strategies, and Applications - Céline Laroche (Marine Drugs, 2022)
Microalgae and cyanobacteria are photosynthetic organisms that can produce/accumulate biomolecules with industrial interest. Among these molecules, EPSs are macromolecular polysaccharidic compounds that present biological activities and physico-chemical properties, allowing to consider their valorization in diverse commercial markets, such as cosmetic, therapeutic, nutraceutic, or hydrocolloids areas. The number of microalgae and cyanobacteria strains described to produce such EPSs has increased in recent years as, among the 256 producing strains gathered in this review, 86 were published in the last 10 years (~33%). Moreover, with the rise of research on microalgae EPSs, a variety of monosaccharides compositions have been discovered, highlighting the versatility of these organisms. If some production strategies can be applied to increase EPS production yields, it appears that case by case studies are needed to promote EPS synthesis by a strain, as many responses exist. This paper proposes an up-to-date state of the art of the diversity of microalgae and cyanobacteria EPS-producing strains, associated to the variability of compositions. The strategies for the production and extraction of the polymers are also discussed. Finally, an overview of the biological activities and physico-chemical properties allow one to consider their use on several commercial markets.